Endothelin Signaling Contributes to Modulation of Nociception in Early-stage Tongue Cancer in Rats. (June 2018) - Furukawa, Akihiko; Shinoda, Masamichi; Kubo, Asako; Honda, Kuniya; Akasaka, Ryuta; Yonehara, Yoshiyuki; Iwata, Koichi
Abstract : Background: Patients with early stage tongue cancer do not frequently complain of tongue pain. Endothelin-1 signaling is upregulated in the cancerous tongue at the early stage. We tested the hypothesis that endothelin-1 signaling contributes to the modulation of tongue nociception. Methods: Squamous cell carcinoma cells were inoculated into the tongue under general anesthesia. Lingual mechanical sensitivity under light anesthesia using forceps from days 1 to 21 (n = 8) and the amounts of endothelin-1 and β-endorphin in the tongue on days 6, 14, and 21 (n = 5 to 7) were examined after the inoculation. The effect of endothelin-A or µ-opioid receptor antagonism on the mechanical sensitivity was examined (n = 5 to 7). Results: Lingual mechanical sensitivity did not change at the early stage (days 5 to 6) but increased at the late stage (days 13 to 14). The amount of endothelin-1 increased (25.4 ± 4.8 pg/ml vs. 15.0 ± 5.2 pg/ml; P = 0.008), and endothelin-A receptor antagonism in the tongue induced mechanical hypersensitivity at the early stage (51 ± 9 g vs. 81 ± 6 g; P = 0.0001). The µ-opioid receptor antagonism enhanced mechanical hypersensitivity (39 ± 7 g vs. 81 ± 6 g; P < 0.0001), and the amount of β-endorphin increased at the early stage. Conclusions: β-Endorphin released from the cancer cells via endothelin-1 signaling is involved in analgesic action in mechanical hypersensitivity at the early stage. Abstract : Using a model of squamous cell carcinoma of the tongue, levels of endothelin-1 and β-endorphin were found to be increased at an early stage. The enhanced expression of β-endorphin in early stage tongue cancers may conceal their presence.